Circulating maternal and umbilical cord steroid hormone and insulin-like growth factor concentrations in twin and singleton pregnancies. (8th October 2018) - Houghton, L. C.; Lauria, M.; Maas, P.; Stanczyk, F. Z.; Hoover, R. N.; Troisi, R.
Abstract: In addition to being associated with a higher risk of complications during pregnancy, twinning may also be a proxy for altered hormonal exposure for mothers and twin offspring, with implications for their health later in life. We compared maternal and fetal steroid hormone and insulin-like growth factor concentrations between singleton ( n =62) and twin ( n =41) pregnancies. Maternal concentrations of androgens, estrogens, insulin-like growth factor (IGF)-1, IGF-binding protein (BP)-3 and prolactin were quantified during the third trimester and at delivery, as well as in the fetal circulation at birth. Geometric means accounting for gestational age were calculated for hormone concentrations and compared between matched twin and singleton pregnancies. Most maternal hormone concentrations were modestly higher in twin than in singleton pregnancies in the third trimester (ranging from 8.3% for IGF-1 to 17.1% for estradiol) and at delivery (ranging from 11.1% for IGFBP-3 to 15.2% for estriol). Cord serum hormones were generally similar in twin and singleton pregnancies, except for IGFBP-3, which was 200% lower in twins. The modest differences in maternal hormones in late gestation seem unlikely to explain alterations in hormonally related disease risk in mothers of twins compared with singletons. The large deficit of IGFBP-3 in the fetal circulation of twins at birth may allow for sufficient concentrations of IGF-2 for growth and development in an environment of shared nutritional resources.